Kesejahteraan Guru: Kunci Peningkatan Kualitas Pengajaran di Sekolah Dasar - Wawan Syahputra; Wildan Sajali Harap; Cut Kumala Sari (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Teacher welfare is a crucial factor in determining the quality of teaching, especially at the elementary school level which is the foundation of children's education. This article aims to examine the relationship between teacher welfare and improving the quality of teaching. Through a qualitative approach with literature study and descriptive analysis, it was found that welfare which includes financial, emotional, social, and professional aspects has a direct impact on teacher motivation, performance, and interaction in the classroom. The results of this study recommend increasing attention to teacher welfare as a key strategy in elementary education reform.